Pumpkin Rind and Seeds Extracts Inhibit α - Glucosidase and Nitric Oxide Production and Promote Chlorella ellipsoidea Growth in Culture - Yongkhamcha, Butsara; Buddhakala, Nopparat (Trends in Sciences, 2023)
The objective of this work was to investigate the potential of pumpkin rind and seed on antidiabetic and anti-inflammatory activities and the underlying mechanism. Therefore, this work was carried out to determine the antidiabetic activity using inhibitory activities of pumpkin rind and seeds extracts on α - glucosidase and the anti-inflammatory activity via inhibitory activity on nitric oxide production. And also, the potential of the pumpkin rind and seeds on culture of Chlorella ellipsoidea was determined. Determination of inhibitory activity on α - glucosidase was performed using α - glucosidase assay, while the Griess assay was employed for the inhibition on Nitric oxide (NO) -production. The pumpkin seed extract inhibited α - glucosidase more potent than the pumpkin rind extract (IC50 of 321.36 vs. 326.18 µg/mL). However, the activities of the extracts were less potent than that of Acarbose (IC50 of 317.26 µg/mL). Application of the extracts at the highest concentration, 500 µg/mL, the pumpkin seed extract displayed the inhibition of NO production higher than the pumpkin rind extract did (18.01 ± 1.57 % vs. 14.99 ± 1.94 %). Study on the effects of pumpkin rind and seeds on C. ellipsoidea culture revealed that the optimum media was the 7th medium (NPK+ mixture of pumpkin seed water and Blue-Green Medium (BG-11), 1:4) which generated the growth of C. ellipsoidea for 28 days with the Optical Density (OD) value of 1.43 ± 0.01 followed by BG-11 medium OD value of 1.41 ± 0.02) and the 3rd medium (NPK+ mixture of pumpkin rind water and BG-11, 1:1, OD value of 1.32 ± 0.01), respectively. The chemical contents of C. ellipsoidea cultured in 7th medium contained 54.25 ± 0.06 % protein, 15.95 ± 0.87 % carbohydrates, 9.35 ± 0.05 % fat, and 20.30 ± 0.33 % ash, meanwhile 53.37 ± 0.77 % protein, 12.83 ± 0.62 % carbohydrates, 17.80 ± 0.23 % fat, and 23.30 ± 1.33 % ash in the 3rd medium. The results obtained from this investigation indicate that pumpkin rind and seeds not only can be exploited for the antidiabetic and anti-inflammatory components but also can be applied instead of the conventional medium for the culture of C. ellipdoidea. Therefore, bio-waste from pumpkin could be potentially utilized as the source of natural antidiabetic inhibitors, anti-inflammatory drugs and the effective components of C. ellipdoidea culture media. HIGHLIGHTS The pumpkin rind and seed extracts possess antidiabetic and anti-inflammatory properties The extracts from pumpkin rind and seeds exhibit antidiabetic activity via α- glucosidase inhibition The extracts from pumpkin rind and seeds display anti-inflammatory activity by inhibiting on nitric oxide (NO) production The extracts from pumpkin rind and seeds could be potentially utilized as a source of natural antidiabetic inhibitors and anti-inflammatory drugs The bio-waste, pumpkin rind and seeds, could be used as the effective components of ellipdoidea culture medium GRAPHICAL ABSTRACT